When does x^3+y^3+z^3-3xyz equals to zero?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This doesn't prove there are no other equality cases.
x 3 + y 3 + z 3 − 3 x y z = ( x + y + z ) ( x 2 + y 2 + z 2 − x y − y z − z x ) = 0
⟺ either x + y + z = 0 or
x 2 + y 2 + z 2 − x y − y z − z x = 0
⟺ ( x − y ) 2 + ( y − z ) 2 + ( z − x ) 2 = 0 ⟺ x = y = z .
Log in to reply
This is the standard solution. Nice job.
Log in to reply
William, just key in "\ " and "\ " before and after x^3 + y^3 + z^3 - 3xyz and you will get perfect x 3 + y 3 + z 3 − 3 x y z in LaTex.
Problem Loading...
Note Loading...
Set Loading...
x 3 + y 3 + z 3 x 3 + y 3 + z 3 − 3 x y z = ( x + y + z ) ( x 2 + y 2 + z 2 ) − ( x y + y z + z x ) ( x + y + z ) + 3 x y z = ( x + y + z ) ( x 2 + y 2 + z 2 ) − ( x y + y z + z x ) ( x + y + z )
When x + y + z = 0 :
⇒ x 3 + y 3 + z 3 − 3 x y z = ( 0 ) ( x 2 + y 2 + z 2 ) − ( x y + y z + z x ) ( 0 ) = 0
When x = y = z :
⇒ x 3 + y 3 + z 3 − 3 x y z = 3 x 3 − 3 x 3 = 0